(untitled) (Research, Society and Development, 2020)
Aromatherapy, is an ancient complementary therapeutic technique that uses essential oil from aromatic plants in order to provide physical well-being and mental. There are different oils used in this practice, such as Rosmarinus officinalis (rosemary), which has stimulating and anxiolytic activity. This study aimed to identify the main scientific works carried out in vivo with the essential oil of rosemary and to verify the complementary therapeutic potential of this medicinal plant. The systematic review carried out used data available in the CAPES journals (Scopus, Web of Science, Pubmed and Scielo), using the keyword “Aromatherapy”. Documents were included from 2010, written in English, French, Spanish and Portuguese that carried out in vivo tests with rosemary essential oil or mixtures included in this plant. From this search, only thirteen scientific articles published in Turkey, Hungary, United States, Thailand, Iran, Japan and Germany were selected; where most of the tests were performed on the human species (84.62%). The most used method in the experiments was the inhalation of essential oils (61.54%), being used 30.77% pure rosemary oil and 69.23% mixtures containing this species. Conclude whether the pure rosemary essential oil using the inhalation method shows a stimulating and anti-stress effect in humans and improves cognitive function in Alzheimer’s dementia in mice.